2018
DOI: 10.21548/39-2-2782
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Application of Several Nitrogen Sources as Fertilisers to Tempranillo Grapevines: Effect on Wine Volatile Composition

Abstract: Foliar nitrogen applications to the vineyard make it possible to improve grape and wine phenolic and amino acid concentration. However, to our knowledge, there is little information about their impacts on the volatile composition of wine. Therefore, the aim of this work was to evaluate the effects of the application of several nitrogen sources in Tempranillo vineyards on wine volatile composition during the first season. Subsequently, two dosages of phenylalanine and urea were applied to the vineyard with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Nevertheless, MeJ wines were characterized by a lower content of isoamyl acetate, 2-phenylethyl acetate and total acetate esters when compared with MeJ+Ur wines (Figure 1a-c). Ancín-Azpilicueta et al [24] showed a decrease in isoamyl acetate in urea wines with respect to the content of control wines, whereas Rubio-Bretón et al [25] did not show differences in this compound between control and urea wines. Figure 1d-j show the ethyl esters content in the wines.…”
Section: Effect Of the Foliar Mej And Mej+ur Applications On Wine Aro...mentioning
confidence: 91%
See 4 more Smart Citations
“…Nevertheless, MeJ wines were characterized by a lower content of isoamyl acetate, 2-phenylethyl acetate and total acetate esters when compared with MeJ+Ur wines (Figure 1a-c). Ancín-Azpilicueta et al [24] showed a decrease in isoamyl acetate in urea wines with respect to the content of control wines, whereas Rubio-Bretón et al [25] did not show differences in this compound between control and urea wines. Figure 1d-j show the ethyl esters content in the wines.…”
Section: Effect Of the Foliar Mej And Mej+ur Applications On Wine Aro...mentioning
confidence: 91%
“…Moreover, differences in total alcohol content were not found (Figure 2g). Rubio-Bretón et al [25], in their study about different nitrogen foliar applications to vineyard, concluded that the content of alcohols in wines was scarcely affected by urea foliar application, whereas Ancín-Azpilicueta et al [24] described a decrease in the total concentration of higher alcohols in wines elaborated with grapes from vines treated with urea, as was observed in MeJ+Ur wines, in the first season. On the other hand, Gómez-Plaza et al [13] showed an increase in certain alcohols and in the total alcohols content in MeJ wines in contrast with the results described in this work in both seasons studied (Figure 2).…”
Section: Effect Of the Foliar Mej And Mej+ur Applications On Wine Aro...mentioning
confidence: 98%
See 3 more Smart Citations